2006
DOI: 10.1083/jcb.200506033
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen transactivates EGFR via the sphingosine 1-phosphate receptor Edg-3: the role of sphingosine kinase-1

Abstract: The transactivation of enhanced growth factor receptor (EGFR) by G protein–coupled receptor (GPCR) ligands is recognized as an important signaling mechanism in the regulation of complex biological processes, such as cancer development. Estrogen (E2), which is a steroid hormone that is intimately implicated in breast cancer, has also been suggested to function via EGFR transactivation. In this study, we demonstrate that E2-induced EGFR transactivation in human breast cancer cells is driven via a novel signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
193
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(211 citation statements)
references
References 35 publications
(95 reference statements)
15
193
0
1
Order By: Relevance
“…SphK1, a major enzyme that generates S1P, was found to be overexpressed in lung patient samples [43]. The SphK/S1P pathway was shown to mediate the E2-induced transactivation of EGFR, which is associated with carcinogenesis in lung cancer cells [44]. It has also been reported that expression of the oncogenic K-Ras leads to plasma membrane localization of SphK1 and increased S1P level [45].…”
Section: S1p and Related Signaling In Lung Cancermentioning
confidence: 98%
“…SphK1, a major enzyme that generates S1P, was found to be overexpressed in lung patient samples [43]. The SphK/S1P pathway was shown to mediate the E2-induced transactivation of EGFR, which is associated with carcinogenesis in lung cancer cells [44]. It has also been reported that expression of the oncogenic K-Ras leads to plasma membrane localization of SphK1 and increased S1P level [45].…”
Section: S1p and Related Signaling In Lung Cancermentioning
confidence: 98%
“…Since most of GPR30-expressing tissues are considered to be ER positive, it seems likely to assume that their estrogenic responses are partially mediated by GPR30. GPR30 demonstrably regulates the phosphorylation state of ERK1/2 [86,87,88], induces mobilisation of intracellular calcium [89,90], cAMP (cyclic adenosine monophosphate) release [87], and synthesis of phosphoinositide 3-kinase (PI3K) [90]. In the course of mER signalling, a trans-activation of epithelial growth factor receptor (EGFR), IGF-1 receptor, and human epithelial growth factor receptor type 2/neu (Her-2/neu) occurs, leading to the activation of their downstream mediators ERK1/2 and PI3K/Akt [87].…”
Section: Estrogen Receptor Transcriptionmentioning
confidence: 99%
“…Activated S1P 3 , in turn, enhances downstream signaling including EGFR transactivation and ERK phosphorylation [57,60]. A recent study demonstrated that both Estradiol and S1P induce rapid internalization of membrane EGFR while sustaining cytosolic/ endosome EGFR levels, indicating a delay in degradation of the EGFR [43].…”
Section: Luminal A: Er/pr-positive and Her2-negativementioning
confidence: 99%
“…The most predominantly expressed S1PR in MCF-7 cells is S1P 3 and it is capable of being activated by both Estradiol and S1P [57,[60][61][62][63]. Activated S1P 3 , in turn, enhances downstream signaling including EGFR transactivation and ERK phosphorylation [57,60].…”
Section: Luminal A: Er/pr-positive and Her2-negativementioning
confidence: 99%
See 1 more Smart Citation